2021
DOI: 10.1080/02699931.2021.1941783
|View full text |Cite
|
Sign up to set email alerts
|

Reactance, morality, and disgust: the relationship between affective dispositions and compliance with official health recommendations during the COVID-19 pandemic

Abstract: Reactance, morality, and disgust: The relationship between affective dispositions and compliance with official health recommendations during the COVID-19 pandemic.Emergency situations require individuals to make important changes in their behavior. In the case of the COVID-19 pandemic, official recommendations to avoid the spread of the virus include costly behaviors such as self-quarantining or drastically diminishing social contacts. Compliance (or lack thereof) with these recommendations is a controversial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 42 publications
6
45
2
2
Order By: Relevance
“…Inconsistent with previous research (Chan, 2021;Ekici et al, 2021;Pagliaro et al, 2021), we did not see that individualizing foundations predicted more self-reported COVID-19 prevention behaviors, but we did see that binding foundations were related to reporting fewer prevention behaviors such as hand-washing, masking, and social-distancing. This is contrary to recent research in a French population that found that endorsing the binding foundations of authority and purity were associated with increased prevention behaviors (Díaz and Cova, 2021), suggesting that the effects we found may be unique to the U.S. American population. Indeed, the COVID-19 pandemic is more politicized and polarized in the United States than other countries (Mordecai and Connaughton, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Inconsistent with previous research (Chan, 2021;Ekici et al, 2021;Pagliaro et al, 2021), we did not see that individualizing foundations predicted more self-reported COVID-19 prevention behaviors, but we did see that binding foundations were related to reporting fewer prevention behaviors such as hand-washing, masking, and social-distancing. This is contrary to recent research in a French population that found that endorsing the binding foundations of authority and purity were associated with increased prevention behaviors (Díaz and Cova, 2021), suggesting that the effects we found may be unique to the U.S. American population. Indeed, the COVID-19 pandemic is more politicized and polarized in the United States than other countries (Mordecai and Connaughton, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, participants who endorsed the moral foundations of care, fairness, and purity were more likely to rate a target who missed a sibling's wedding more favorably if they did so to minimize COVID-19 exposure than for another reason. Additionally, research has found that endorsement of care (Díaz and Cova, 2021) and fairness foundations (Chan, 2021) predicted more COVID-19 prevention behaviors. Some evidence suggests that this is because individualizing foundations predict a greater trust in science (Pagliaro et al, 2021).…”
Section: Moral Foundations and Covid-19mentioning
confidence: 99%
“…Indeed, in a study investigating empathic emotional reactions to others affected by COVID-19, participants with higher empathic concern for others, or those who were exposed to an elderly person affected by COVID-19, reported increased intended and actual behaviors related to physical distancing and mask wearing [ 59 ]. In another study, measures of perspective taking and empathic concern were found to significantly predict adherence to guidelines ([ 56 ]; for similar findings regarding perspective taking, see [ 60 ]).…”
Section: Introductionmentioning
confidence: 81%
“…In particular, an internal locus of control appears to buffer COVID-related stress [ 37 ] and mental burden [ 38 ], additionally promoting medication compliance and health-related behaviour [ 39 , 40 ]. Previous evidence on the relation between COVID-19 disease concern and sensitivity to moral wrongdoing [ 41 ] suggests that adherence to containment measures is also driven by moral values [ 42 ]. Finally, personality traits have been shown to reflect adaptive decision-making drivers such as obtaining rewards, avoiding punishments, and managing uncertainty.…”
Section: Introductionmentioning
confidence: 99%